O professor e a prática educativa - Silveira, Eraneci da Costa (1984)
This work intends to analise teaching deve 1 opment and practice held in the three first grades of grade school, in seven public schools of the urbanic periphery of Sant'~ Ana do Livramento, RS. It started due to criticism made to pedagogical work at public schools. Those carne from different segments of our sociaty which complained about the distance between the way of operating school knowlegde and the real needs of a concrete subject. Interviews, to analise the basic teaching and class tutoring, to verify the concents of transformation process of the studies, were some of the methods used to obtain a better work. The concluding analises were: - The goals aimed by the teaching strategies are seldom reached. - The only moment you can do find a relation between teaching and practice is through the weak students. lV'ork with - The tendency is to use a common ~ay of pedagical action which overvalues the quantitative aspects of learning. - The teaching value in upper classes has reproduced the discerning role of education through ways which the majority of the population to receive school educatian.The teachers transfer to extra-institutional factors the guilt of education failure. This behavior identifies the protétting mechanism against the pedagogical method which neither reduces nor eliminates the obstacles between school and popular knowlegde.